Influence of Sodium Chloride (NaCl) Deposition on the Atmospheric Corrosion of Galvanized Steel Roofing - Muhammad Zakwan bin Amran, Muhammad Zakwan (Universiti Teknologi Petronas, 2010)
This paper is a report on the research and study of the atmospheric corrosion behavior of galvanized steel roofing under the influence of Sodium Chloride (NaCl) deposition. This research focus on the atmospheric corrosion behavior of galvanized steel roofing under the application in the marine environment which exposed directly to the extreme environment of sea weather with high exposure to Sodium Chloride deposition. ASTM B 117 Salt Spray (Fog) Test and Mass Loss Method are introduced to study the corrosion behavior of galvanized steel under different concentration of Sodium Chloride (NaCl) concentration. The exposure time was set to four weeks for each concentration. The result from the experiments was gathered in a table and graph was plotted to show the influence of the NaCl deposition on the atmospheric corrosion of galvanized steel roofing. The results show that Sodium Chloride can accelerate the atmospheric corrosion of the galvanized steel roofing. After 4 weeks of exposure, the corrosion rate increase as the NaCl concentration increase. However, the corrosion rate decrease as the time of exposure elapses from week 1 to week 4. This behavior is due to the electrochemical process that takes place on the surface of the galvanized steel as discussed in chapter 4 of this report.